Methods of spectral analysis in the control system of an arc extinguishing reactor - A. D. Dubkova; S. Yu. Dolinger; D. S. Osipov (Омский научный вестник)
In this article the method of automatic setup of the adjustable arc-suppressing reactor using a surge characteristic of a circuit of the zero sequence of a distributive network for determination of natural frequency and parameters of a circuit is considered. In this method it is used wavelet conversion and the nonparametric analysis for determination of natural frequency of a circuit of the zero sequence. In the article results of operation of a method of automatic setup of the arc-suppressing reactor when using different algorithms of the nonparametric analysis in case of determination of natural frequency are provided.